Modern classification of bone tumors according to who (iv edition, 2013 year). comments of pathologist - Hryhorovskyi, Valeriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
An article is devoted to modern classification of bone tumors according WHO (2013) and contains short historical facts about its preceding issues, division on section in new issue, definition of certain nosological entities and pathologist’s comments, based on author’s experience according to the results of clinical-morphological investigation of more than ten thousands clinical cases. The main sections of classification of bone tumors according WHO (2013) are: chondrogenic, osteogenic, fibrogenic, fibrohistiocytic, hematopoietic neoplsmas, tumors rich in osteoclastic giant cells, notochordal, vascular, myogenic, lipogenic tumors, lesions with unidentified neoplastic nature, various tumors. Data concerning immunohistochemical and genetic peculiarities of cells and tissues, which are important for differential diagnostics and prediction of clinical behavior, are given in each section for the most significant, from point of view of histopathologist’s practice, diseases. Some special issues are reviewed in the article, such as: malignity grade of bone tumors; diseases with unidentified neoplastic nature; tumorous syndromes (congenital diseases that more comparing with any other in whole population can lead to tumors of bones and soft tissues). It was emphasized in the article that bone tumors classification according to WHO accumulated achievements in the investigation of pathology, clinics, genetics, imaging procedures, pharmacology and it should become an unifying textbook for physician of different specialities dealing with the problems of diagnostics and treatment of patients with oncopathology of locomotor system.